Promosi Kesehatan tentang Post Natal Yoga di Wilayah Kerja Puskesmas Kebun Kopi - Nurbaiti Nurbaiti; Laida Sanilpa Tiwi (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The postpartum period begins when the placenta is born and ends when the uterine organs return to their pre-pregnancy state. During the postpartum period, they will experience physical and psychological changes, physical changes include the ligaments becoming soft and loose, the tense muscles of the uterus enlarging, posture The body changes to compensate for weight changes during pregnancy. Postpartum care is needed because it is a critical period for both mother and baby. Yoga is a type of body, mind and mental exercise that really helps mothers to strengthen their pelvic muscles, abdominal muscles and reposition the spine in a correct and good position, improve body posture, reduce discomfort in postpartum mothers. This community service activity aims to Mothers' knowledge and understanding increased, this activity was carried out in the Working Area of the Kopi Garden Community Health Center and was carried out on December 20 2021. The target of this activity was post partum mothers, totaling 20 people. The method used was lectures, discussions and questions and answers, using leaflet media, to measure the team's knowledge of performingpre test with good knowledge results of 8 (40%), poor knowledge of 12 (60%), and after education was carried out to determine the increase in mother's knowledge, it was carried outpost test and the results obtained were good knowledge of 16 (80%) while poor knowledge was 4 (20%), so it can be seen that there was an increase in the mother's knowledge before and after the education. As a result of this activity, the mother's knowledge increased and the mother wanted to apply yoga independently at home.